2009
DOI: 10.1007/s00268-009-0262-5
|View full text |Cite|
|
Sign up to set email alerts
|

Reexcision of Soft Tissue Sarcoma: Sufficient Local Control but Increased Rate of Metastasis

Abstract: Despite an incomplete initial resection, reexcision enables local control similar to that in patients without residual tumor. Still, these patients have a worse prognosis owing to an increased rate of distant metastasis; therefore, patients with soft tissue masses of unknown identity should be transferred to centers that specialize in treating sarcomas for adequate initial resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
1
38
1
4
Order By: Relevance
“…This is so despite that for those cases with positive surgical margins referred from LH, re‐surgery is a standard procedure in the RC involved in this analysis (HSE). Other authors too have found survival impact for cases referred after unplanned surgeries, with the prognostic impact being higher in cases with residual disease at the time of re‐excision . Data of microscopical residual disease at re‐excision were not analyzed in our series, so we cannot confirm this finding as critical for worse RFS.…”
Section: Discussionmentioning
confidence: 75%
“…This is so despite that for those cases with positive surgical margins referred from LH, re‐surgery is a standard procedure in the RC involved in this analysis (HSE). Other authors too have found survival impact for cases referred after unplanned surgeries, with the prognostic impact being higher in cases with residual disease at the time of re‐excision . Data of microscopical residual disease at re‐excision were not analyzed in our series, so we cannot confirm this finding as critical for worse RFS.…”
Section: Discussionmentioning
confidence: 75%
“…2, 3, 810 However, when comparing tumor bed excision following unplanned excision to planned complete excision as the initial procedure, some studies have observed inferior overall oncologic outcomes even when repeat resection is performed, suggesting that there is an adverse oncologic effect of unplanned excision. 6, 7 Conversely, other studies have shown equivalent oncologic outcomes between matched cohorts of tumor bed excision patients after unplanned excision compared to planned complete excision as the initial procedure, suggesting that oncologic outcomes are dictated by final surgical results.…”
Section: Discussionmentioning
confidence: 99%
“…Principally, adequate re-excision has been said to improve local and systemic tumor control, or even overall survival, compared to single adequate primary tumor excision [ 23 , 24 ]. Other studies, however, have shown higher local recurrence rates, impaired prognosis and increased rates of metastasis even after sufficient re-excision [ 3 , 6 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%